Endogenous Pancreatic β Cell Regeneration: A Potential Strategy for the Recovery of β Cell Deficiency in Diabetes - Zhong, Fan; Jiang, Yan (Frontiers in Endocrinology, 2019)
Endogenous pancreatic β cell regeneration is a potential strategy for β cell expansion or neogenesis to treat diabetes. Regeneration can occur through stimulation of existing β cell replication or conversion of other pancreatic cells into β cells. Recently, various strategies and approaches for stimulation of endogenous β cell regeneration have been evaluated, but they were not suitable for clinical application. In this paper, we comprehensively review these strategies, and further discuss various factors involved in regulation of β cell regeneration under physiological or pathological conditions, such as mediators, transcription factors, signaling pathways, and potential pharmaceutical drugs. Furthermore, we discuss possible reasons for the failure of regenerative medicines in clinical trials, and possible strategies for improving β cell regeneration. As β cell heterogeneity and plasticity determines their function and environmental adaptability, we focus on β cell subtype markers and discuss the importance of research evaluating the characteristics of new β cells. In addition, based on the autoimmunologic features of type 1 diabetes, NOD/Lt-SCID-IL2rgnull (NSG) mice grafted with human immune cells and β cells are recommended for use in evaluation of antidiabetic regenerative medicines. This review will further understand current advances in endogenous β cell regeneration, and provide potential new strategies for the treatment of diabetes focused on cell therapy.